Nanocellulose-based fiber as well as preparation method and application thereof

By mixing bacterial cellulose with sodium alginate, natural polyphenols and metal iron element and treating it through a solidification bath, nanocellulose-based fibers with excellent flame retardant and photothermal antibacterial properties are prepared, which solves the problem of poor performance of nanocellulose-based fibers in the prior art, and realizes the functional development of efficient and environmentally friendly cellulose fibers.

CN119859864AActive Publication Date: 2025-04-22SICHUAN UNIV +2
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510073158.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-22
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

The flame retardant and photothermal antibacterial properties of existing nanocellulose-based fibers are not ideal enough, and it is difficult to meet the high requirements in medical materials such as biological auxiliary materials.

Method used

The bacterial cellulose dispersion is oxidized and mixed with sodium alginate, natural polyphenols and metal iron element to form a spinning raw liquid. After the solidification bath treatment is treated, nanocellulose-based fibers are prepared. This method etches iron element through natural polyphenols to form a metal phenolic network, imparts antibacterial and flame retardant properties to the fibers, and enhances the overall strength of the fibers by crosslinking iron ions with cellulose and sodium alginate.

Benefits of technology

The prepared nanocellulose-based fibers have significant flame retardant properties and efficient photothermal antibacterial effects, with an antibacterial effect of ≥99%, and their flame retardant properties are better than cotton fibers. The process is pollution-free and the process is green and environmentally friendly.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859864A_ABST
    Figure CN119859864A_ABST
Patent Text Reader

Abstract

The invention discloses a nanocellulose-based fiber as well as a preparation method and application thereof, belongs to the technical field of cellulose spinning, and solves the problem that the flame-retardant and antibacterial performance effects of the nanocellulose-based fiber in the prior art are not ideal. The method comprises the following steps: uniformly mixing an oxidized bacterial cellulose dispersion liquid and a sodium alginate / natural polyphenol-iron solution to obtain a spinning stock solution; wherein the mass ratio of the oxidized bacterial cellulose to the sodium alginate is 1: (0.5-2.0); extruding the spinning solution into a coagulating bath to form continuous gel filaments, soaking the gel filaments in the coagulating bath, and cleaning the gel filaments in deionized water; and drying to obtain the nanocellulose-based fiber. The nanocellulose-based fiber provided by the invention has excellent flame-retardant and photo-thermal antibacterial properties, the preparation process is pollution-free, the process is green and environment-friendly, and the technology has great reference significance for functional development, green processing and deep development of cellulose fibers.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of cellulose spinning, and more specifically to a nano-cellulose-based fiber and a preparation method and application thereof. Background Art

[0002] The development of high-performance and functional fiber products has greatly enriched people's daily lives. However, while bringing convenience, chemical fiber fabrics that are difficult to degrade have also caused serious environmental pollution. Therefore, it is of great significance to find and develop alternative biodegradable fibers. The research on the fiberization of biomass such as cellulose has gradually attracted more attention from academia and industry. However, the current commercial regenerated cellulose fibers have complex production processes, high production costs, and serious solvent system pollution, making it difficult to achieve truly green processing and development of cellulose fibers. In recent years, researchers have prepared nanocellulose by physical or chemical methods. Based on its excellent mechanical properties, high specific surface area, high hydrophilicity and biocompatibility, nanocellulose has been widely used in various fields. Among them, nanocellulose prepared by TEMPO oxidation has a high aspect ratio and uniform size distribution. The repulsion between the negative charges on the surface of the nanocellulose not only promotes the stripping of nanocellulose, but also facilitates its uniform dispersion in water. Using oxidized cellulose nanofibers as a matrix and adding biomass polymers to improve the continuity of spinning has the possibility of forming high-strength fibers.

[0003] However, in the application of medical materials such as biological excipients, the requirements for the flame retardant and photothermal antibacterial properties of nanocellulose and fibers are higher than those of ordinary fibers, and existing products are difficult to achieve the ideal effect. Therefore, nanocellulose-based fibers with flame retardant and photothermal antibacterial properties and their preparation methods are urgently to be discovered. Summary of the invention

[0004] The present invention provides a nano-cellulose-based fiber and a preparation method and application thereof, which are used to solve the problem that the flame retardant and antibacterial effects of the nano-cellulose-based fiber in the prior art are not ideal.

[0005] In the first aspect, the present invention provides a method for preparing nanocellulose-based fibers, comprising the following steps: subjecting a bacterial cellulose dispersion to oxidation treatment to obtain an oxidized bacterial cellulose dispersion; dissolving sodium alginate in ultrapure water, adding natural polyphenols under continuous stirring conditions, stirring until the solution is uniform, adding iron, and continuously stirring until the solution turns dark purple to obtain a sodium alginate / natural polyphenol-iron solution; uniformly mixing the oxidized bacterial cellulose dispersion and the sodium alginate / natural polyphenol-iron solution to obtain a spinning solution; wherein the mass ratio of oxidized bacterial cellulose to sodium alginate is 1:0.5-2.0; extruding the spinning solution into a coagulation bath to form continuous gel filaments and washing them in deionized water after soaking them in a coagulation bath; and drying to obtain the nanocellulose-based fibers. wherein the iron can be in different forms such as iron nails, iron rods, iron blocks, and iron sheets, which are not specifically limited in this application.

[0006] As a possible implementation, the bacterial cellulose dispersion is a non-derivatized bacterial cellulose dispersion with a mass percentage of 3wt% to 8wt% obtained by mechanical shearing and homogenization; and / or, the sodium alginate is dissolved in ultrapure water, and its mass percentage in the ultrapure water is 3wt% to 8wt%; and / or, natural polyphenols are added, and its mass percentage in the ultrapure water is 0.3wt% to 0.8wt%; and / or, the continuous stirring is carried out until the solution turns dark purple, and the stirring time is 20 to 30 hours; and / or, the mass percentage of the spinning solution is 3wt% to 8wt%.

[0007] As a possible implementation, the natural polyphenol is any one of tannic acid, gallic acid, catechin and catechol; and / or the coagulation bath is a calcium chloride aqueous solution; and / or the mass concentration of the coagulation bath is 1%wt to 5%wt.

[0008] As a possible implementation method, the oxidation treatment includes the following steps: adjusting the pH of the bacterial cellulose dispersion to 10-10.5 with an alkaline solution, adding 2,2,6,6-tetramethylpiperidine-nitrogen-oxide and sodium bromide, and adding a sodium hypochlorite solution with a pH of 10-10.5; stirring at room temperature and maintaining the pH at 10-10.5 with an alkaline solution, adding ethanol to quench the reaction after it is fully reacted, and filtering to obtain the oxidized bacterial cellulose dispersion.

[0009] As a possible implementation manner, the mass ratio of the bacterial cellulose in the bacterial cellulose dispersion, the 2,2,6,6-tetramethylpiperidine-nitrogen-oxide, the sodium bromide and the sodium hypochlorite in the sodium hypochlorite solution is 1:0.016-0.02:0.1-0.125:0.2235-0.2794; and / or, the stirring rate at room temperature is 450-550 rpm; and / or, the alkaline solution is a sodium hydroxide solution.

[0010] In a second aspect, the present invention provides a nanocellulose-based fiber prepared by the method described in any possible implementation of the first aspect.

[0011] As a possible implementation, the flame retardant properties of the nanocellulose-based fibers are significantly better than those of cotton fibers.

[0012] As a possible implementation method, the antibacterial effect of the nanocellulose-based fiber is ≥ 99%.

[0013] As a possible implementation manner, the antibacterial effect is: an effect of resisting Staphylococcus aureus and / or Escherichia coli.

[0014] In a third aspect, the present invention provides a use of the nanocellulose-based fibers prepared by the method described in any possible implementation of the first aspect or the nanocellulose-based fibers described in any possible implementation of the second aspect in medical materials.

[0015] As a possible implementation, the medical material includes biological excipients.

[0016] The nanocellulose-based fibers provided by the present invention are prepared from oxidized bacterial nanocellulose fibers, sodium alginate, natural polyphenols and metallic iron. The natural polyphenols can etch the iron and form a metal phenolic network with iron ions, thereby giving the target product antibacterial and flame retardant functions. At the same time, the iron ions can also be cross-linked with oxidized cellulose and sodium alginate to enhance the overall strength of the target product.

[0017] The nanocellulose-based fibers provided by the present invention have excellent flame retardant and photothermal antibacterial properties, and the preparation process is pollution-free and the process is green and environmentally friendly. This technology has great reference significance for the functional development, green processing and deep development of cellulose fibers. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0019] Figure 1 Ultraviolet spectrum detection results and physical pictures of the Alg / TA-Fe solution provided in the embodiment of the present invention.

[0020] Figure 2 Pictures of various spinning solutions (above) and pictures of various product fibers (below) provided for embodiments of the present invention, wherein a represents product A, b represents product B, and c represents product C.

[0021] Figure 3 The strength test results of each fiber provided in the embodiment of the present invention, wherein a is the breaking strength curve and b is the breaking elongation.

[0022] Figure 4 The fiber surface and cross-sectional morphology images of each fiber measured by electron microscopy provided in the embodiments of the present invention, wherein a represents sodium alginate fiber D, b represents sodium alginate fiber E, c represents Alg / TAFe2-TOBC1 fiber, d represents Alg / TAFe1-TOBC1 fiber, and e represents Alg / TAFe2-TOBC2 fiber.

[0023] Figure 5 The flame retardant test results of various fibers provided in the embodiments of the present invention.

[0024] Figure 6 The micro-caloric test results of each fiber provided in the embodiments of the present invention.

[0025] Figure 7 The antibacterial performance results of various fibers provided in the embodiments of the present invention. DETAILED DESCRIPTION

[0026] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] In order to solve the problem that the flame retardant and antibacterial effects of nano-cellulose-based fibers in the prior art are not ideal, the embodiments of the present invention provide a preparation, characterization and testing experiment of nano-cellulose-based fibers.

[0028] The bacterial cellulose dispersion is subjected to oxidation treatment to obtain an oxidized bacterial cellulose dispersion; sodium alginate is dissolved in ultrapure water, natural polyphenol is added under continuous stirring conditions, the solution is stirred until it is uniform, iron is added, and the solution is continuously stirred until it turns dark purple to obtain a sodium alginate / natural polyphenol-iron solution; the oxidized bacterial cellulose dispersion and the sodium alginate / natural polyphenol-iron solution are uniformly mixed to obtain a spinning solution; wherein the mass ratio of the oxidized bacterial cellulose to the sodium alginate is 1:0.5-2.0; the spinning solution is extruded into a coagulation bath to form continuous gel filaments, which are soaked in a coagulation bath and then washed in deionized water; and nanocellulose-based fibers are obtained after drying.

[0029] In the present invention, the bacterial cellulose dispersion is a non-derivatized bacterial cellulose dispersion with a mass percentage of 3wt% to 8wt% obtained by mechanical shearing and homogenization; natural polyphenols are added, and the mass percentage of natural polyphenols in ultrapure water is 0.3wt% to 0.8wt%; the solution is continuously stirred until it turns dark purple, and the stirring time is 20 to 30 hours; the mass percentage of the spinning solution is 3wt% to 8wt%.

[0030] The technical solutions of the present invention under the above conditions can obtain the target product, and the mechanical properties, flame retardant properties, photothermal properties and antibacterial efficacy of the target product can achieve ideal effects. In the specific experiment, the preparation of product A, product B and product C was taken as an example for characterization and testing. It is proved that the nanocellulose-based fiber provided by the present invention has excellent mechanical properties, flame retardant properties, photothermal properties and antibacterial efficacy.

[0031] The technical solution of the present invention will be further described below in conjunction with specific embodiments.

[0032] Example 1

[0033] This embodiment provides an experiment for preparing nanocellulose-based fibers.

[0034] Bacterial cellulose colloid was used as raw material, mechanically sheared and dried, and then sheared, crushed and homogenized (600MPa) by a high-pressure homogenizer for 30 times to obtain a bacterial cellulose dispersion with a mass fraction of 3wt%. Sufficient sodium hydroxide solution was added to the bacterial cellulose dispersion (100g) until the pH reached about 10, and 2,2,6,6-tetramethylpiperidine-nitrogen-oxide (TEMPO, 0.016g, 0.1mmol) and sodium bromide (NaBr, 0.1g, 1mmol) were added. The pH of 5wt% sodium hypochlorite (NaClO) solution was adjusted to 10 by adding hydrochloric acid. NaClO solution was added at a dose of 3mmolNaClO / gram of cellulose to start TEMPO-mediated oxidation, and sodium hydroxide solution was continuously added at room temperature with stirring at 500rpm to maintain the pH at 10-10.5. After 6 hours of reaction, ethanol was added for quenching. Filtered to obtain an oxidized bacterial cellulose dispersion, filtered and washed thoroughly with water, and stored at 4°C. Dissolve 900 mg of sodium alginate (Alg) in 30 mL of ultrapure water (mass percentage is 3 wt%). Then, add 90 mg of tannic acid (TA) to the Alg solution under continuous stirring, stir until the mixed solution is uniform, and transfer to a 50 mL centrifuge tube. Immerse a clean iron nail in the mixed solution and stir continuously for 24 hours. The color of the solution gradually changes from light yellow to pink and finally to dark purple, obtaining a sodium alginate / tannic acid-iron solution (Alg / TA-Fe solution). The prepared Alg / TA-Fe solution is subjected to ultraviolet spectroscopy detection, and the TA-Fe solution without adding Alg is used as a comparison, and the following is obtained. Figure 1 The results shown. Figure 1 It can be seen that the color of Alg / TA-Fe and TA-Fe solutions gradually changed from colorless to dark black and dark purple, indicating that TA etches the iron nails and releases Fe 3+ , forming a TA-Fe complex; observing the UV spectrum, it can be seen that the presence of the Alg-Fe network causes the ligand to metal charge transfer (LMCT) band of TA-Fe to blue-shift; the Alg / TA-Fe system jointly realizes the continuous assembly of the TA-Fe network, forming a metal phenolic network and a sodium alginate-metal network structure.

[0035] Preparation of product A (Alg / TAFe2-TOBC1): The prepared Alg / TA-Fe solution and oxidized bacterial cellulose dispersion (3wt%) were mixed at room temperature in a mass ratio of 2:1 to obtain Alg / TAFe2-TOBC1 spinning solution, which was centrifuged to remove bubbles. The Alg / TAFe2-TOBC1 spinning solution was extruded by an injection pump (11.6m / min) and then washed in a multi-coagulation bath to obtain Alg / TAFe2-TOBC1 fibers, wherein the coagulation bath was a CaCl2 solution with a mass fraction of 1wt%. After exiting the coagulation bath from the guide roller, the fibers were heat dried and finally collected by traction through a winding roller.

[0036] Preparation of product B (Alg / TAFe1-TOBC1): The prepared Alg / TA-Fe solution and oxidized bacterial cellulose dispersion (3wt%) were mixed at room temperature in a mass ratio of 1:1 to obtain Alg / TAFe1-TOBC1 spinning solution, which was centrifuged to remove bubbles. The Alg / TAFe1-TOBC1 spinning solution was extruded by an injection pump (11.6m / min) and then washed in a multi-coagulation bath to obtain Alg / TAFe1-TOBC1 fibers, wherein the coagulation bath was a CaCl2 solution with a mass fraction of 1wt%. After exiting the coagulation bath from the guide roller, the fibers were heat dried and finally collected by traction of a winding roller.

[0037] Preparation of product C (Alg / TAFe2-TOBC2): The prepared Alg / TA-Fe solution and oxidized bacterial cellulose dispersion (3wt%) were mixed at room temperature in a mass ratio of 1:2 to obtain Alg / TAFe2-TOBC2 spinning solution, which was centrifuged to remove bubbles. The Alg / TAFe2-TOBC2 spinning solution was extruded by an injection pump (11.6m / min) and then washed in a multi-coagulation bath to obtain Alg / TAFe2-TOBC2 fibers, wherein the coagulation bath was a CaCl2 solution with a mass fraction of 1wt%. After exiting the coagulation bath from the guide roller, the fibers were heat dried and finally collected by traction through a winding roller.

[0038] The spinning solutions and fibers in the prepared products A, B and C are as follows: Figure 2 As shown, it can be seen that the scheme provided by the present invention successfully prepared Alg / TAFe2-TOBC1 spinning solution, Alg / TAFe1-TOBC1 spinning solution and Alg / TAFe2-TOBC2 spinning solution; as well as Alg / TAFe2-TOBC1 fiber, Alg / TAFe1-TOBC1 fiber and Alg / TAFe2-TOBC2 fiber.

[0039] Preparation of product D (Alg): 900 mg of sodium alginate was dissolved in 29.1 mL of deionized water to prepare a sodium alginate spinning solution with a mass fraction of 3 wt%. The sodium alginate spinning solution was extruded through a spinneret (11.6 m / min) into a coagulation bath, wherein the coagulation bath was a 1 wt % CaCl2 aqueous solution. The solution was washed in a water bath to remove residual Ca 2+ After washing, heat drying and stretching, sodium alginate fiber D is obtained.

[0040] Preparation of product E (Alg / TA-Fe): The prepared Alg / TA-Fe solution was extruded as spinning solution through a spinneret (11.6 m / min) into a coagulation bath, wherein the coagulation bath was a 1 wt% CaCl2 aqueous solution. The solution was washed in a water bath to remove residual Ca 2+ After washing, heat drying and stretching, sodium alginate fiber E is obtained.

[0041] Example 2

[0042] This example provides a characterization experiment of nanocellulose-based fibers.

[0043] Spinning confirmation: In this embodiment, wet spinning is used to perform spinning confirmation on the spinning solution to be tested.

[0044] Ultraviolet absorption spectrum: The test was carried out using a UV-visible spectrophotometer (U-3900, China).

[0045] Characterization of colloid rheology: A digital viscometer (SNB-2, China) was used to test the spinning solution. 50 mL was placed in a beaker and allowed to stand for 24 h. The solution was measured using an L4 rotor at room temperature of 25 °C. The unit of measurement was mPa·s.

[0046] Characterization of single fiber mechanical properties: The mechanical properties of the tested fibers were tested using an electronic single yarn strength tester (YM061, China). The clamp distance was set to 30 mm, the tensile speed was fixed at 10 mm / min, and each sample was measured 5 times to take the average value, and the dry strength (cN / dtex) and elongation at break (%) were calculated and recorded.

[0047] Fiber morphology characterization: Scanning electron microscopy (FEIQuanta 200, USA) was used to test the microscopic morphology of the fiber surface and cross section. Liquid nitrogen brittle fracture treatment was used for the complete sample preparation of the fiber cross section.

[0048] Flame retardant properties: The flame retardant properties of the fibers to be tested were tested using a microcalorimeter (MCC-2, manufactured by Comac). The test weight of each sample was 5 mg. Cotton was used as a comparison.

[0049] Photothermal test: 10 mg of the fiber to be tested was cut into pieces of about 1 cm in length and placed in a 1.5 mL centrifuge tube. Infrared light (808 nm, 1 W / cm 2 ) irradiation.

[0050] Photothermal antibacterial: Staphylococcus aureus (S. aureus) and Escherichia coli (E. coli) were used as model bacteria; 10 mg of the fiber to be tested was sterilized by irradiation with ultraviolet light for 15 min and then placed in a 1.5 mL centrifuge tube, and 0.2 mL of 10 7 CFU / mL bacterial suspension, and then infrared irradiation for 10 min; the experimental group was placed in a shaker at 37°C for 0.5 h, and then diluted to 10 3 CFU / mL bacterial solution was plated and counted.

[0051] In this example, the Alg / TAFe2-TOBC1 spinning solution, Alg / TAFe1-TOBC1 spinning solution, Alg / TAFe2-TOBC2 spinning solution, sodium alginate spinning solution and Alg / TA-Fe solution in Example 1 were used as spinning solutions to be tested; Alg / TAFe2-TOBC1 fiber, Alg / TAFe1-TOBC1 fiber, Alg / TAFe2-TOBC2 fiber, sodium alginate fiber D and sodium alginate fiber E were used as fibers to be tested for various characterizations and tests, and the results were as shown in Tables 1 and 2. Figure 2 Results shown.

[0052] Table 1 Characterization and test results

[0053]

[0054] The characterization results of the single fiber mechanical properties of each fiber are shown in Figure 3 The fiber morphology characterization results of each fiber are shown in Figure 4 ,Depend on Figure 3 It can be seen that the tensile breaking strength of Alg / TAFe2-TOBC1 fiber, Alg / TAFe1-TOBC1 fiber and Alg / TAFe2-TOBC2 fiber is 1.609-2.366 cN / dtex, which is significantly higher than that of sodium alginate fiber D and sodium alginate fiber E. This is because during the spinning process, the nanocellulose is highly oriented and assembled under the action of tensile force, see Figure 4 In c, d and e, the prepared fibers are highly oriented and have a dense structure. As the proportion of cellulose increases, the fibers are arranged regularly. Figure 4In e1, a close-up of the surface of a single Alg / TAFe1-TOBC2 filament is shown, and a wrinkled texture along its long axis is observed, which is attributed to the lateral shrinkage during the drying process, and this lateral shrinkage should further contribute to the orientation of the embedded fibers. In a single alginate fiber D, the fibers are evenly distributed and oriented almost parallel to their long axis.

[0055] The flame retardant test results of each fiber are shown in Figure 5 ,Depend on Figure 5 It can be seen that the integral area of ​​the heat release curve of cotton fiber is the largest, indicating that cotton fiber is highly flammable; while sodium alginate fiber has a smaller total heat release (THR) and maximum heat release rate (PHRR), and the corresponding heat release peak moves to 222°C; with the increase of nanocellulose content, the total heat release and maximum heat release rate of the fiber increase as expected, but after adding 33% cellulose nanofibers, it is still lower than that of sodium alginate fiber. Even if the total solid content of cellulose reaches 66%, its total heat release (THR) and maximum heat release rate are still much lower than cotton fiber. It is speculated that Fe 3+ The presence of Fe can significantly reduce the PHRR of CNF. 3+ The presence of catalyzes the thermal decomposition of nanocellulose, producing non-combustible gas and water, which takes away most of the heat, thereby reducing the heat released by cellulose.

[0056] The photothermal test results of each fiber are shown in Figure 6 The results of the photothermal antibacterial efficacy of each fiber are shown in Figure 7 , from Table 1, Figure 6 and Figure 7 It can be seen that compared with sodium alginate fibers, Alg / TAFe2-TOBC1 fibers, Alg / TAFe1-TOBC1 fibers and Alg / TAFe2-TOBC2 fibers all have excellent photothermal properties, and can be heated to above 60°C after 5 minutes of infrared light irradiation. And no matter what proportion of nanocellulose-based fibers, the antibacterial effect is about 99%, showing good photothermal antibacterial properties. The survival rate of cells after growing on the fibers for 1 day is 99.9%. In summary, the prepared nanocellulose-based fibers with flame retardant and photothermal antibacterial properties have excellent functionality and are expected to be used in the field of medical materials such as biological dressings.

[0057] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.

[0058] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.

Claims

1. A method for preparing nanocellulose-based fibers, characterized in that: The following steps are involved: The bacterial cellulose dispersion is subjected to oxidation treatment to obtain an oxidized bacterial cellulose dispersion; Dissolve sodium alginate in ultrapure water, add natural polyphenols under continuous stirring, stir until the solution is uniform, add iron, and continue stirring until the solution turns dark purple to obtain a sodium alginate / natural polyphenol-iron solution; The oxidized bacterial cellulose dispersion and the sodium alginate / natural polyphenol-iron solution are uniformly mixed to obtain a spinning solution; wherein the mass ratio of the oxidized bacterial cellulose to the sodium alginate is 1:0.5-2.0; The spinning solution is extruded into a coagulation bath to form continuous gel filaments, which are then soaked in the coagulation bath and then washed in deionized water; the nano-cellulose-based fibers are obtained after drying.

2. The preparation method according to claim 1, characterized in that: The bacterial cellulose dispersion is a non-derivatized bacterial cellulose dispersion having a mass percentage of 3wt% to 8wt% obtained by mechanical shearing and homogenization; And / or, the sodium alginate is dissolved in ultrapure water, and its mass percentage in the ultrapure water is 3wt% to 8wt%; And / or, the natural polyphenols are added in an amount of 0.3wt% to 0.8wt% by mass in the ultrapure water; And / or, the continuous stirring is performed until the solution turns dark purple, and the stirring time is 20 to 30 hours; And / or, the mass percentage of the spinning solution is 3wt% to 8wt%.

3. The preparation method according to claim 1, characterized in that: The natural polyphenol is any one of tannic acid, gallic acid, catechin and catechol; And / or, the coagulation bath is a calcium chloride aqueous solution; And / or, the mass concentration of the coagulation bath is 1%wt to 5%wt.

4. The preparation method according to claim 1, characterized in that: The oxidation treatment comprises the following steps: The pH of the bacterial cellulose dispersion is adjusted to 10 to 10.5 with an alkaline solution, 2,2,6,6-tetramethylpiperidine-nitrogen-oxide and sodium bromide are added, and a sodium hypochlorite solution with a pH of 10 to 10.5 is added; The mixture is stirred at room temperature and the pH value is maintained at 10 to 10.5 with an alkaline solution. After the reaction is complete, ethanol is added for quenching, and the mixture is filtered to obtain the oxidized bacterial cellulose dispersion.

5. The nanocellulose-based fiber prepared by the preparation method according to any one of claims 1 to 4.

6. The nanocellulose-based fiber according to claim 5, characterized in that Its flame retardant properties are significantly better than cotton fibers.

7. The nanocellulose-based fiber according to claim 5, characterized in that Its antibacterial effect is ≥99%.

8. The nanocellulose-based fiber according to claim 7, characterized in that The antibacterial effect is: the effect of resisting Staphylococcus aureus and / or Escherichia coli.

9. Use of the nanocellulose-based fiber prepared by the preparation method according to any one of claims 1 to 4 or the nanocellulose-based fiber according to any one of claims 6 to 8 in medical materials.

10. The use according to claim 9, characterized in that: The medical materials include biological excipients.

Citation Information

Patent Citations

  • Bacterial cellulose nano fiber based directionally-arranged macro fiber and preparation method thereof

    CN105926065A

  • Preparation method of composite fiber of cellulose nanometer fibrils / alginate

    CN106521706A

  • Semi-interpenetrating network cellulose-based hydrocolloid material for spinning as well as preparation method and application of semi-interpenetrating network cellulose-based hydrocolloid material

    CN119161594A

  • Multi-stage pore hydrogel medicament sustained-release system based on natural polyphenol and preparation method therefor

    WO2024045224A1